Sentinels of Science Awards - Agapiou, Athos (My University, 2026)
Top 1% reviewers in the field of Remote Sensing for 2017. Publons Top 1% reviewers in the field of Social Sciences for 2017. Publons Top 1% reviewers in the field of Earth and Planetary Sciences for 2017. Publons
Keywords: Sciences